The Influence of Organizational Culture on the Improvement of Health Services at Telaga Murni Public Health Center - Donah Mulatsih; Agus Cholik; Anita Wijayanti; Sri Wahyuni; Sumantoro (International Publisher, 2024)
This study explores the influence of organizational culture on the improvement of health services at the Telagamurni Public Health Center. Using an explanatory survey method with a quantitative approach, the study analyzed data from 89 respondents selected through stratified random sampling. The findings reveal that organizational culture contributes 68.5% to the improvement of health service quality. The dimension of team orientation scored the highest, emphasizing the importance of collaboration in health services. Conversely, the aspects of innovation and risk-taking recorded the lowest scores, indicating the need for enhancements in organizational creativity and adaptability. Practical implications of these findings include strengthening training programs, developing integrated health information systems, and implementing digital transformation in health services.